Light of Hope: Symbolism and Narratives in Visual Arts - Gong, Xiaojian; Chettasurat, Boontan; Sukna, Suchat (วารสารศิลปกรรมบูรพา, 2024)
This study presents an investigation into the symbolic significance of light, hope, and ships in visual art through an iterative process of documentary analysis and design creation. The aims were 1) to craft and analyze contemporary visual design pieces that utilize light as a medium to symbolically represent hope; 2) to create designs inspired by the enduring image of ancient Chinese sailboats; and 3) to explore and illuminating the complex interplay of resilience, aspiration, and guidance inherent in human experience. Initial sketches serve as preliminary visual representations, evolving into final designs through the experimental use of various materials and equipment, including LEDs, steel wire, fence net, electric welding machines, and ribbons. These materials were chosen considering both their symbolic and aesthetic contributions to the designs. Prototypes were constructed and continually refined, resulting in final designs that were then analyzed and documented. The entire process from initial concept to final creation was rigorously documented, providing both visual and narrative records of the creative journey. The resulting designs offer a nuanced reflection on hope, utilizing ships and light as central motifs to symbolize life’s journey towards optimism. The study highlights the intrinsic link between the chosen materials and symbols, where wood represents the natural instinct of seeking and hoping; steel epitomizes strength and resilience; and bamboo, noted for its flexibility, mirrors human adaptability amidst adversities. Each material is not only historic and practical but also metaphorical, adding layers to the narrative of hope and aspiration. Through a systematic exploration of themes, the study illuminates the intertwined relationships of hope, light, and journey, contributing to a holistic understanding of these themes in visual design.